2014
DOI: 10.1080/20445911.2014.946419
|View full text |Cite
|
Sign up to set email alerts
|

Shifts of spatial attention cued by irrelevant numbers: Electrophysiological evidence from a target discrimination task

Abstract: Fischer et al. demonstrated that a centrally presented number can shift attention to the left/right when its magnitude is small/large. Two electrophysiological studies described these attentional effects as eventrelated potentials (ERPs) at centro-parietal sites. Since both studies used target detection tasks, it remains currently unknown whether similar results would be obtained with a discrimination task. We used ERPs to test whether digit cues also induce attention shifts when participants perform a feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…The present findings support the view of a primary role of gaze direction in shifting visuospatial attention (i.e., premotor theory of spatial attention; see Casarotti et al, 2012) that, as a consequence, can affect number processing. Correlational studies (e.g., neuroimaging studies: Knops et al, 2009) and studies reporting shifts of spatial attention following the processing of number magnitudes (e. g., Fischer et al, 2003;Ranzini et al, 2009;Schuller et al, 2014) provide interesting information about the cognitive and neural architecture of the numerical (and spatial) domain but do not allow to disentangle between a functional role of spatial attention and eye movements in number processing or a mere epiphenomenal effect. In the present study, instead, we report evidence supporting the first view, showing that a manipulation of spatial attention through eye movements can modulate performance in a numerical task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings support the view of a primary role of gaze direction in shifting visuospatial attention (i.e., premotor theory of spatial attention; see Casarotti et al, 2012) that, as a consequence, can affect number processing. Correlational studies (e.g., neuroimaging studies: Knops et al, 2009) and studies reporting shifts of spatial attention following the processing of number magnitudes (e. g., Fischer et al, 2003;Ranzini et al, 2009;Schuller et al, 2014) provide interesting information about the cognitive and neural architecture of the numerical (and spatial) domain but do not allow to disentangle between a functional role of spatial attention and eye movements in number processing or a mere epiphenomenal effect. In the present study, instead, we report evidence supporting the first view, showing that a manipulation of spatial attention through eye movements can modulate performance in a numerical task.…”
Section: Discussionmentioning
confidence: 99%
“…The main finding is that number processing facilitates the visual processing of targets located in the left or right side of space according to numerical magnitude in a cued detection paradigm (Fischer, Castel, Dodd, & Pratt, 2003; also see Dodd, Van der Stigchel, Adil Leghari, Fung, & Kingstone, 2008;Galfano, Rusconi, & Umiltà, 2006; for electrophysiological evidence, see Ranzini, Dehaene, Piazza, & Hubbard, 2009;Schuller, Hoffmann, & Schiltz, 2014) or temporal order judgement (Casarotti, Michielin, Zorzi, & Umiltà, 2007). Other studies have reported that number processing induces spatial biases in both healthy participants (e.g., de Hevia, Girelli, & Vallar, 2006;Fischer, 2001;Nicholls, Loftus, & Gevers, 2008) and brain-damaged patients (e.g., Bonato, Priftis, Marenzi, & Zorzi, 2008;Loftus, Nicholls, Mattingley, & Bradshaw, 2008a).…”
mentioning
confidence: 94%
“…saccade planning and execution) may be dissociated. Such dissociations of components are not uncommon, for example, dissociations of various signatures of attention deployment, such as EEG signatures without accompanying behavioural correlates (Sallilas, El Yagoubi, & Semenza, 2008;Schuller, Hoffmann, Goffaux, & Schiltz, 2015). Furthermore, saccades and ocular drift differentially modulate neuronal activity (Kagan, Gur, & Snodderly, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, individuals tend to respond faster to smaller numerosities with the left hand and to lager numerosities with the right hand (at least in Western societies who read in the left-to-right direction), a phenomenon known as SNARC (Spatial Numerical Association of Response Codes) effect (Dehaene, Bossini & Giraux, 1993). Furthermore, processing numerical magnitude can orient attention to different portions of external space (small numbers biasing attention to the left, while large numbers bias to the right) (e.g., Cattaneo, Fantino, Tinti, Silvanto & Vecchi, 2010; Di Luca, Pesenti, Vallar & Girelli, 2013; Fischer, 2001; Goffaux, Martin, Dormal, Goebel & Schiltz, 2012; Schuller, Hoffmann, Goffaux & Schiltz, 2014). Accordingly, Loetscher, Bockisch, Nicholls and Brugger (2010) measured participants’ eye position during a random number generation task and found that a leftward and downward change in eye position predicted that the next number would be smaller than the last.…”
Section: Introductionmentioning
confidence: 99%